ANALYSIS OF OCCUPATIONAL SAFETY AND HEALTH RISK MANAGEMENT ON THE AMPHIBIOUS OPERATIONS EXERCISE USING HIRARC METHOD - Yudha Sukma Perdana; Sutrisno Sutrisno; Udisubakti Cipto Mulyono (JOURNAL ASRO, 2021)
To Keep Indonesian defense, the TNI has one of the main tasks, namely carrying out War Military Operations (OMP). One form of this operation is the amphibious operation, which is a military operation launched from the sea by the Indonesian Navy's marine units and landing troops loaded on ships and involving air power. In its implementation, amphibious operations exercises contain potential risks that can endanger the safety of personnel and defense equipment materials. Several accidents in amphibious operations have been experienced by the Indonesian Navy. The purpose of this study is to determine the risks that exist in amphibious operation activities and then measure the risk value in amphibious operation activities so that risk control proposals can be made. The method used in this study is HIRARC. The HIRARC method is widely used in the world and is very suitable to be applied in conducting a risk analysis because it is considered complete enough to include the process of risk identification, risk assessment and risk control. Based on the risk analysis using HIRARC, it is known that amphibious operation training activities have 84 potential risks with 19 risks at the extreme level, 27 risks at the high level, 29 risks at the moderate level and 9 risks at the low level. While the highest risk value is in the attack stage with a risk value of 297. With the research results that have been obtained, several proposals for risk control and appropriate risk mitigation can be proposed in order to realize the Navy towards zero accident. Keywords: Amphibious Operation, Risk Management, HIRARC